Numerical modeling of hydrodynamic circulation in Ichkeul Lake-Tunisia. (February 2020) - Ouni, H.; Sousa, M.C.; Ribeiro, A.S.; Pinheiro, J.; Ben M'Barek, N.; Tarhouni, J.; Tlatli-Hariga, Nejla; Dias, J.M.
Abstract: The Ichkeul Lake ecosystem, Northern of Tunisia, has been registered as a biosphere reserve in 1977 (MAB-UNESCO Convention), a UNESCO World Heritage site in 1979, and a RAMSAR site in 1980. Damming and global warming drought drastically diminished the fresh water supply to this lake. This leads to water level and salinity fluctuation throughout the year. Consequently, the water clarity of this shallow wind-stressed lake was altered and if this siltation continues to increase, will seriously affects the hydromorphology and ecology of this wetland. Therefore, to study the hydrodynamic water circulation in the lake and the transport of the Total Suspend Matter (TSM), hydrodynamic and transport models were calibrated and applied to this environment. Numerical model predictions based on water level, temperature and salinity sensitivity to the bed roughness show that the Delft 3D-Flow model reproduced well the measured data with RMSE < 0.027 for water level.